RUSSIAN-BELARUSIAN BORDER REGION AS AN INTERCAPITAL REGION - A. P. Katrovskiy; A. K. Nizhnikova (Наука. Инновации. Технологии, 2022)
Introduction and problem statement. It is noted that the intercapital location as a type of inter-central geographical posi- tion generates a special type of spatial inequality between capitals (metropolitan regions) and their hinterlands. None of the regions of the Union State is experiencing such a strong impact on its development from the capitals and capital regions as the Russian-Belarusian borderland. Qualitative and functional differences (development inequality) turn into quantitative differences (economic growth inequality). Territorial socioeconomic polarization has become the most important feature of economic dynamics in the inter-capital space. Data and methods. Territorial inequalities have been revealed by applying statistical and spatial analysis to the statistical data. In addition to spatial analysis, the study uses comparative geographical and cartographic methods. The provisions of the center-periphery theory as well as those of growth poles and development and production-territorial systems have been the theoretical basis of the research. The research findings and discussion. The study revealed significant socio-economic inequalities between the capital regions and the ones of the Russian-Belarusian border areas. Structural inequalities have increased for the post-Soviet period what eventually has led to signiicant quantitative inequalities. The gap between successful metropolitan areas and inter-capital periphery is widening. The uniqueness of the situation lies in the fact that development the metropolitan regions being a positive process of changes in the economic structure is at the same time accompanied by the economic degradation of inter-capital areas where the share of high-tech industries is decreasing. The concentration of population, cultural and scientific potential and higher education in Moscow and Minsk has a "toxic effect" on the development of periphery of the inter-capital space, creates "lacunae" on certain territories of the Russian-Belarusian borderland. Conclusions. The most important feature of the economic transformation of the Russian-Belar- usian border areas is the increasing trend for these regions to become the periphery. It is especially obvious when it comes to the increasing share of the capitals and metropolitan regions in the development of the most creative and high-tech industries. With little state regulation in the field of regional policy Minsk and Moscow are developing as "total" capitals "pumping" intellectual capital out of the border regions. Their structural degradation can be stopped only by way of adopting a different regional policy, aimed at the development of higher education, creative and high-tech industries.